2021
DOI: 10.3390/ijms222413277
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Human Transcriptomics Data in the Context of Peritoneal Dialysis Identifies Novel Receptor-Ligand Interactions as Potential Therapeutic Targets

Abstract: Peritoneal dialysis (PD) is one therapeutic option for patients with end-stage kidney disease (ESKD). Molecular profiling of samples from PD patients using different Omics technologies has led to the discovery of dysregulated molecular processes due to PD treatment in recent years. In particular, a number of transcriptomics (TX) datasets are currently available in the public domain in the context of PD. We set out to perform a meta-analysis of TX datasets to identify dysregulated receptor-ligand interactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The authors further focused on receptor-receptor complexes and receptor-ligand interactions and found that six and 70 were uniquely dysregulated, respectively. In the latter group, extracellular matrix (ECM) organization driven by integrin subunit beta 1 (ITGB1) and ITGB2 was most prominent [11]. This study highlights that angiogenesis and mechanisms involved in ECM re-organization play a pivotal role in patients undergoing chronic PD treatment.…”
mentioning
confidence: 88%
“…The authors further focused on receptor-receptor complexes and receptor-ligand interactions and found that six and 70 were uniquely dysregulated, respectively. In the latter group, extracellular matrix (ECM) organization driven by integrin subunit beta 1 (ITGB1) and ITGB2 was most prominent [11]. This study highlights that angiogenesis and mechanisms involved in ECM re-organization play a pivotal role in patients undergoing chronic PD treatment.…”
mentioning
confidence: 88%